PENGATURAN PEMILIHAN UMUM DAN PEMILIHAN KEPALA DAERAH YANG EFEKTIF PASCA PERUBAHAN UUD 1945 SEBAGAI WUJUD NEGARA HUKUM YANG DEMOKRATIS - Hindiawati, Wahyu (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2024)
The amendments to the 1945 Constitution have brought about quite basic changes to the general election system and regional heag elections in Indonesia. Reform is a democratic step that was born in Indonesia. The law has regulated general election of general elections and regional head regulation of general elections and regional head elections, there are still many obstacles. For this reason, the writer formulates the problem as follows: How are the Effective Regulations for General Elections and Regional Head Elections after the Amendment to the 1945 Constitution?. The method that bases its analysis on legislation with a historitical approach. The conclusion of this study is that in the general election there is a change in statutory arrangements in general it can be said that the general election is actually centered on the “sovereignty of the people’’ as the legal owner of power in democracy. While in the regional head election, one of the changes is related to filling the position of regional head as regulated in Article 18 paragraph (4) of the 1945 Constitution of the Republic of Indonesia which states that the Governor, Regent dan city governments are elected. Democratically which menas that elections are carried out directly by the people and representatives. Both the general election and regional head elections will run effectively if the are carried out on the principles of being direct, general, free, confidential, honest and fair. If this principle is implemented properly, the Indonesian state will become a democratic legal state